Stereotyp seksbomby w świetle wybranych realizacji filmowych i danych ankietowych (Conversatoria Linguistica, 2019)
This paper presents the stereotype of a sex bomb in the cinema in relation to actresses and their film roles. The opening chapters explain the term stereotype, focusing especially on the sex bomb stereotype and how it has functioned in the cinema. Film stars that are known for their sex appeal and are considered sex bombs, are presented. The paper then focuses on finding the use and motive of a sex bomb creation in films. The last chapter describes the survey that was conducted to investigate the extent to which the sex bomb stereotype functions nowadays. The findings allow to evaluate how the stereotype has been evolving and whether the characteristics assigned to it have changed.